Sharh Ghayat al-murad fi nazm al-i'tiqad - al-Khalili, Ahmad ibn Hamad (Masqat : Wizarat al-Awqaf wa-al-Shu'un al-Diniyah, 2015)
Commentaries on'Umani, Nur al-Din al-Salimi's Ghayat al-murad fi al-i'tiqad; Islamic theology; poems.
Keywords: al-Salimi,'Abd Allah ibn Humayyid, -- approximately 1871-; al-'Umani, Nur al-Din al-Salimi.; Islam -- Doctrines; Islamic poetry, Arabic -- History and criticism; Islam -- Doctrines -- Poetry